Sacroiliitis and Polyarteritis Nodosa in a Patient with Familial Mediterranean Fever - Yunus Ugan; Atalay Doğru; Hüseyin Şencan; Mehmet Şahin; Şevket Ercan Tunç (Case Reports in Medicine)
Familial Mediterranean fever (FMF) is an autoinflammatory disorder with autosomal recessive inheritance, characterized by recurrent fever and episodes of serositis. The condition is known to be caused by mutations in the MEFV (Mediterranean FeVer) gene, located in the short arm of chromosome 16. While more than 310 sequence variants in the MEFV gene have been described to date, the diagnosis is still established clinically. FMF may be accompanied by sacroiliitis and various forms of vasculitis. The most common forms of associated vasculitis are Henoch-Schonlein purpura and polyarteritis nodosa (PAN). We have presented here a fairly rare case of FMF, accompanied by both sacroiliitis and PAN.